A Postpartum Uterine Dehiscence in a Pregnant Woman with Brucellosis; A Cases Report: A uterine dehiscence in a brucellosis case - Mohammadbeigi, Abolfazl; Mirzaie, Monireh; Yazdi, Zahra; Asgarian, Azadeh; Savari, Marzieh (Ethiopian Journal of Reproductive Health, 2023)
Introduction Uterine Dehiscence (UD) is a rare complication and very dangerous complication of cesarean section (CS). Brucellosis is a threatening infection in pregnant women with severe obstetrics outcomes such as spontaneous abortion, premature delivery, intrauterine infection. We presented a case with preterm delivery with continuing high fever due to uterine fascial dehiscence after CS, who were infected to brucellosis. Case: A 26-year-old woman with gravidity 1, referred to the obstetrical department at 30 weeks of gestation due to Preterm Premature rupture of membranes (PPROM). After vaginally sonography, the patient underwent emergency CS due to fetus FHR drop and umbilical cord prolapse. From second day after CS, the patients fever increased and Doppler sonography shows low fluid and hematoma in the uterus and evidence in favor of a lesion collection that was evacuated with laparotomy and uterine fascial dehiscence was detected. Moreover, wound debridement conducted and during laparotomy the adhesions were released. The Wright-Coombs 2ME test showed she was infected to brucellosis. Conclusion: Uterine fascia dehiscence in lower uterine segment incision is a rare but is a potentially dangerous for mothers. However, preterm deliveries due to PPROM and high uncontrolled fever after CS, are conditions that practitioners should considering the uterine dehiscence to their differential diagnoses. Nevertheless, the occurrence of dehiscence due to brucellosis infection is questionable and require more evaluation.